ECLS as an “Airbridge” to Advanced Durable Therapies for Heart Failure - Rizzo, Toni (MD Conference Express, 2014)
Extracorporeal life support (ECLS) may be indicated for patients with refractory cardiogenic shock as a bridge to cardiac transplant or for long-term mechanical circulatory support. In the French territories of the Caribbean, the ECLS is available for emergency cases, but heart transplantation and long-term circulatory assistance are not. This article discusses the feasibility of transatlantic ECLS-assisted patient transfers.